The effect of different rations on ph and volatile fatty acids in the rumen of angora goats - Mehmet KOCABATMAZ; M. Yaşar AKSOYLAR; Zafer DURGUN; Mursayettin EKSEN (Eurasian Journal of Veterinary Sciences)
Three Angora goats of 2 years old and with permanent rumen cannula were used in tihe experiments. Feeding the animals were performed according to 3x3 Latin square desing with 30 day periods. The alfalfa straw and concentrate mixture were fed in the proportions of 80 :20, 60 :40 and 40 : 60 in treatments I, II and III respectively. The rations were given once a day at the 3 % level o'f each goat's body weight.